Lecture notes. - Gulati, Gautam, 1979-; Lynall, Mary-Ellen, 1986-; Saunders, Kate, 1978- (Lecture notes (Blackwell Publishing Ltd.), 2014)
Lecture Notes: Psychiatry provides a concise and accessible introduction to the fundamentals of Psychiatry, presenting the principles of Psychiatric examination followed by systematic coverage of the major psychiatric disorders, as well as covering management and treatment options.This eleventh edition has been revised to include recent developments in history-taking, psychotropic drugs and case presentations, as well as covering the practical elements of patient guidance and care.